Aperture and resolution effects on ultraviolet star-forming properties: insights from local galaxies and implications for high-redshift observations - Clark, Ilyse; Berg, Danielle A.; Leitherer, Claus; Arellano-Córdova, Karla Z.; Sander, Andreas A. C. (The astrophysical journal, 2024)
We present an analysis of the effects of spectral resolution and aperture scale on derived galaxy properties using far-ultraviolet (FUV) spectra of local star-forming galaxies from the International Ultraviolet Explorer (R ∼ 250, field of view (FOV) ∼ 10″ × 20″) and Cosmic Origins Spectrograph on the Hubble Space Telescope (R ∼ 15,000, FOV ∼ 2.″5). Using these spectra, we measured FUV luminosities, spectral slopes, dust attenuation, and equivalent widths. We find that galaxies with one dominant stellar cluster have FUV properties that are independent of aperture size, while galaxies with multiple bright clusters are sensitive to the total light fraction captured by the aperture. Additionally, we find significant correlations between the strength of stellar and interstellar absorption lines and metallicity, indicating metallicity-dependent line-driven stellar winds and interstellar macroscopic gas flows shape stellar and interstellar spectral lines, respectively. The observed line strength versus metallicity relation of stellar-wind lines agrees with the prediction of population synthesis models for young starbursts. In particular, measurements of the strong stellar C iv λλ1548, 1550 line provide an opportunity to determine stellar abundances as a complement to gas-phase abundances. We provide a relation between the equivalent width of the C iv line and the oxygen abundance of the galaxy. We discuss this relation in terms of the stellar-wind properties of massive stars. As the driving lines in stellar winds are mostly ionized iron species, the C iv line may eventually offer a method to probe α-element-to-iron ratios in star-forming galaxies once consistent models with nonsolar abundance ratios are available. These results have important implications for the galaxy-scale, low-resolution observations of high-redshift galaxies from JWST (R ∼ 100-3500).